Study of Characteristic Equation of the Elastic Stress Field near Bimaterial Notche - Arabi, H.; Mirsayar, M.M.; Samaei, A.T.; Darandeh, M. (Проблемы прочности, 2013)
Fracture occurs at interface corners due to stress singularity which generates as a result of material discontinuity and geometrical configuration. In elastic stress field near a bimaterial notch tip, eigenvalues extracted from Airy’s stress function approach determine the order of singularity. In this paper, the characteristic equation of elastic stress field near bimaterial notches is investigated. The study is done on singular eigenvalues as well as the first non-singular eigenvalue which has not been well studied before. First, different combination of materials and geometrical configurations for two of the most applicable paths in the Bogy diagram (β = 0, β = α/4) were studied and the results were comprehensively discussed. It was shown that the geometrical and materials configurations near a bimaterial notch tip can significantly affect on the stress singularity near these corners. Finally, the areas between two lines β = 0 and β = α/4 in the Bogy diagram with high stress singularities were determined and discussed for both the first and second singular eigenvalue. Исследуется характеристическое уравнение для упругого поля напряжений у вершины надреза на стыке двух материалов. Установлено, что разрушение происходит в угловых точках их
стыка из-за возникновения сингулярных напряжений вследствие разрыва сплошности материала и особенностей геометрической конфигурации. В поле упругих напряжений у вершины
надреза на стыке двух материалов порядок такой сингулярности определяют собственные
значения функции напряжений Эри. Выполнен анализ сингулярных собственных значений и
малоизученного первого несингулярного собственного значения. Рассмотрены различные комбинации материалов и геометрических конфигураций для двух наиболее используемых траекторий на диаграмме Боги (β = 0, β = α/4) и детально проанализированы полученные результаты. Показано, что геометрические конфигурации и комбинации материалов у вершины
надреза существенно влияют на сингулярность напряжений вблизи угловых точек надреза.
Области с высокой сингулярностью напряжений были выделены между линиями β = 0 и
β = α/4 на диаграмме Боги и проанализированы как для первого, так и второго сингулярного
собственного значения. Досліджується характеристичне рівняння для пружного поля напружень у
вістрі надрізу на стику двох матеріалів. Установлено, що руйнування відбувається в кутових точках їх стику через виникнення сингулярних напружень
внаслідок розриву суцільності матеріалу й особливостей геометричної конфігурації. У полі пружних напружень у вістрі надрізу на стику двох матеріалів порядок такої сингулярності визначають власні значення функції напружень Ері. Проаналізовано сингулярні власні значення і маловивчене перше несингулярне власне значення. Розглянуто різні комбінації матеріалів і геометричних конфігурацій для двох найбільш використовуваних траєкторій на
діаграмі Богі (β = 0, β = α/4) та детально проаналізовано отримані результати. Показано, що геометричні конфігурації і комбінації матеріалів у вістрі
надрізу суттєво впливають на сингулярність напружень поблизу кутових
точок надрізу. Області з високою сингулярністю напружень виділено між
лініями β = 0 і β = α/4 на діаграмі Богі і проаналізовано як для першого, так
і другого сингулярного власного значення.